Bibliometric Analysis of Islamic Finance Within the Halal Sector Industry - Dini Lestari; Wiryono, Sudarso Kaderi (Journal Integration of Management Studies, 2023)
The possibility of integration between the halal industry and with Islamic financial system can compromise the moving-forward promising business processes that are eligible on the Sharia principle. With the potential for the global, especially the pioneer from predominantly Muslim countries, Islamic finance in the halal industry may be one of the key enablers to support the implementation of growing markets worldwide. This study explores the bibliometric characteristics and trends of Islamic finance and halal business publications indexed in Scopus, Taylor & Francis, ProQuest, Google Scholar, and Crossref. Data were extracted from the five databases used in the paper's research, and free, unbiased searches of all publications published between 1997 and the present were conducted. The terms "Islamic finance" and "halal industry" were employed in this study. The study's methodology is a bibliometric analysis utilizing simple statistical approaches utilizing VOS-viewer software. This analysis discovered trends in document citations, co-citation connections, keyword co-occurrence, and bibliographic coupling. According to the bibliometric investigation, Malaysia and other Muslim-dominated nations produce most journal articles on halal items and Islamic finance. However, most citations come from non-Muslim countries like the United Kingdom. Furthermore, the economic and corporate environment is becoming increasingly important. Economic growth and development of the halal industry with the principle of Islamic finance are substantial as long they get the point of potential in the resource of their countries, not only in the Major-Muslim countries but also non-Muslim countries with promoting the benefits of shariah law. Based on the exciting outcomes, the methodology concern can be chosen as the literature gap in Islamic finance and halal industrial topics.